Comparing the service levels in the European spirits market: A model for evaluating the complexity of a country in the transportation of spirits and an empirical investigation of six different European countries - Martin Göbl; Barbara Niersbach (Journal of Applied Leadership and Management, 2017)
How can the performance of a logistic service level be measured in a consistent way, and how can the measured service level in one country be compared to another country?
Keywords: 650; Supply Chain Management; Supply Chain; Management; Logistics Management; Logistics